The dream train - Wurfel, Marlene (My University, 2021)
You are the hero of this audio adventure through a dreamscape. Happy New Year 2022! Wishing you great sleeps, much growth, and big love. Story, voicework, and audio mix by Marlene Wurfel > www.marlenewurfel.com Train sounds & miscellaneous by: Benboncan; Caquet; Mredig & Inspector J via a Creative Commons Attribution Licence freesound.org https://creativecommons.org/licenses/by/3.0/ Music: A Simple Lullaby by Jesse Keller via Jamendo, Blue Dream by Cheel via YouTube audio library, Sea of Ancestry by Jesse Gallagher via YouTube audio library, Snowy Peaks by Chris Haugen via YouTube audio library. * Emily Carr and Woo are real historical figures you can learn more about :)
Keywords: storytelling; children's stories